Psychological and cultural correlates of illness conception and menopausal symptoms: a cross-sectional and longitudinal comparative study of Mosuo, Yi, and Han women - Gao, Limin; Wang, Jinyi; Zhang, Ying; Zhao, Xudong; Fu, Haojie (Frontiers in Psychiatry, 2025)
ObjectiveThis study explores the differences in menopausal symptoms, illness conception, and health-seeking behaviors among Mosuo, Yi, and Han women in China, analyzes the key factors behind these differences, and conducts a longitudinal comparison.MethodsThis study collected data from Mosuo, Yi, and Han women in Yongning Township, Ninglang County, Yunnan Province, through a questionnaire survey. The instruments included the Kupperman Menopause Index (KMI), Depression-Anxiety-Stress Scale (DASS), Self-Rating Scale of Illness Conception and Health Seeking Behavior (SSICHSB) and General Self-Efficacy Scale (GSES). First, descriptive statistical analysis was conducted on the demographic characteristics and various indicators of the sample. Chi-square tests and one-way ANOVA were used to examine the differences in KMI and SSICHSB among the different ethnic groups. The KMI was used to assess menopausal symptoms, and multiple linear regression analysis was employed to identify the main factors influencing menopausal symptoms. A longitudinal comparison of data from 2012 and 2020 was performed to analyze the dynamic changes in KMI and SSICHSB of Mosuo and Han women.ResultsThe regression analysis identified stress, anxiety, and dysmenorrhea experience as risk factors, while self-efficacy served as a protective factor influencing menopausal symptoms. Both the menopausal symptoms and the scores for concerns and fears about illness among Mosuo women significantly decreased in 2020 compared to 2012 (p = 0.040, p = 0.010).ConclusionThe results provide an important basis for the development of culturally sensitive health interventions. Future public health strategies should consider cultural, social, and physiological factors to provide more effective health support and interventions for women from different ethnic groups.